After the fall German policy in occupied France, 1940-1944 - Laub, Thomas Johnston (Oxford University Press, 2010)
This is a study of the internal conflicts between the German military government, the SS, and the foreign office during the occupation of France, showing how these battles developed and what they implied for the direction of German policy in occupied France from 1940 to 1944.